Pelatihan Implementasi Kurikulum Merdeka Pada Guru di MTs NU 02 Al Ma’arif Boja - Ratih Kusumawati; Arie Wahyuni; Destia Wahyu Hidayati; Lenny Kurniati (DPPM Universitas Pelita Bangsa, 2023)
In the world of education, the thing that is very important and in line with current educational goals is the curriculum. The current education curriculum uses an independent curriculum, some schools now use an independent curriculum because the school system expects the results expected by the school from within and outside. An important role in the placement of this independent curriculum is the teacher. The teacher in the learning process runs the independent curriculum optimally. In this case it will affect the purpose of this community service activity that this community service activity will be able to provide an understanding of the teacher's readiness to implement the independent curriculum in the learning process that will be carried out. This service method uses lecture methods, question and answer, demonstrations and practical exercises. The result of this service is the understanding of participants in implementing the independent curriculum, and participants feel the benefits of this training activity.